Effectiveness of Acceptance and Commitment Therapy on Long-Term Grief Disorder and Reduction of Distress in Coronary Women Nurses - Abtahi Foroshani, Nafiseh; Rakhshan, Parvaneh (Psychology of Woman Journal, 2022)
The aim of this study was to investigate the treatment of acceptance and commitment therapy based on grief disorder and distress among coronary heart disease nurses in the School of Nursing and Midwifery of Shahid Beheshti University of Medical Sciences in Tehran. The present study was a quasi-experimental design of pre-test-post-test with a control group. The experimental sample included 30 bereaved nurses in 1399. They were selected by available sampling method and divided into experimental and control groups. The experimental group underwent group acceptance and commitment therapy training of Professor Steven (1986) for 8 sessions of 60 minutes. The Anxiety Scale (Educational Attendance, Social Attendance, and Cognitive Attendance), Kessler et al. (2002), and the Mourning Questionnaire (1975) were used to collect data on nurses suffering from coronary heart disease due to the spread of the coronavirus online. Data were analyzed using multivariate analysis of covariance in two stages of post-test and follow-up, significance level p